Managing Modular Instruction and Students' Learning Outcomes - Janet D. Barrera; Sweety Rose R. Megallon; Aiwedeh B. Patadlas (PT ARRUS Intelektual Indonesia, 2024)
This study was conducted to determine the level of management of modular instruction in relation to the student’s learning outcomes. The study was conducted among 31 teachers, 12 school heads, 55 parents, and 191 Grade 10 students in Paquito S. Yu Memorial National High School of Lower Timonan, Dulop National High School of Dulop, Dumingag National High School, all of Dumingag Zamboanga del Sur during the School Year 2021-2022. This study used the quantitative-correlational research design. The descriptive statistics included the use of weighted average mean, standard deviation, frequency and percentage distribution; and inferential statistic were done using Kruskal-Wallis test, Spearman-rho correlation and t-test of r using SPSS and online data analysis calculators. The findings revealed that the respondent schools are highly equipped with educational technology to support modular instruction, have modules downloadable through the DepEd websites. The schools have sufficient financial support and material resources and it is properly utilized to sustain the massive reproduction of Self-Learning Modules (SLMs). Teachers were highly trained to manage modular instruction including the preparation of the contents, printing, distribution and assessment. They were also provided with adequate trainings to enrich their content knowledge with integration of educational technology. The contents of the self-learning modules were not only limited to the minimum essential learning competencies, rather it is enriched with in-depth discussions of concepts, visual illustrations, links for demonstrations and short videos. Moreover, the study concluded that the four groups of participants have similar perceptions on the level of management of modular instruction. Most of the student participants have satisfactorily achieved the minimum essential learning competencies in their English subject during the second quarter. The empirical evidence pointed out that even if the schools have highly evident provisions of technology and highly trained teachers, the students’ learning outcomes may not be very impressive. Finally, the study recommends that the Department of Education should allocate an additional budget for modular distance learning modalities; provide teachers with laptops, ensure reliable internet connectivity, provide assistance to teachers, design enhancement activities to improve students' learning outcomes; and encourage parents to support their children. Future researches should focus on the effect of modular instruction on higher-order thinking skills.